Penal Mediation in Juvenile Delinquency Cases in Manado: An Islamic Legal Perspective - Purwadi, Wira; Nasir, Muh.; Alim, Firmansyah Pratama; Selungunaung, Luthfia Syahwa; Awing, Nayla Putri Nisa (IAIN Manado, 2024)
This study analyzes the implementation of penal mediation in cases involving children in conflict with the law in Manado. It examines the obstacles encountered during the penal mediation process in these cases from an Islamic legal perspective. The handling of children in legal matters cannot be equated with the treatment of adults who commit crimes. Penal mediation is an appropriate dispute resolution method for cases involving children, using a restorative justice approach by Islamic law. The research method employed is a normative-empirical approach involving direct interviews with investigators in cases of children in conflict with the law and a literature review examining Islamic law related to the application of juvenile justice. The study reveals that the implementation of penal mediation through diversion has not been fully optimized, as not all juvenile cases are mediated during the processes at the police, prosecutor's office, and court levels. Furthermore, the application of penal mediation in Islamic law aligns with the principles of Islah and Suhl, emphasizing the principle of reconciliation (Islah).